Efektivitas Undang-Undang Perlindungan Konsumen Dalam Menghadapi Peredaran Kosmetik Ilegal di Kota Serang - Erni, Erni; Hasuri, Hasuri (Recital Review, 2025)
This study aims to analyze the effectiveness of the Consumer Protection Law in dealing with the circulation of illegal cosmetics in Serang City. The method used is normative juridical, with a normative analysis approach to applicable legal norms, as well as data collection from legal literature and official documents. The results of the study indicate that although Law No. 8 of 1999 provides a strong legal basis for consumer protection, its effectiveness is still questionable. The high prevalence of illegal cosmetics in the market, lack of human resources at BPOM, and low public awareness of the dangers of illegal cosmetics are the main obstacles in its implementation. BPOM has made various efforts, including supervision and education to the public, but challenges in law enforcement and comprehensive supervision still need to be overcome. Therefore, strategic steps are needed to increase the effectiveness of consumer protection and suppress the circulation of illegal cosmetics in Serang City.